PENGARUH PUPUK LIMBAH CINCAU HITAM TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) - Imam Habibi; Fajar Setyawan; Puji Rahayu (Universitas Tribhuwana Tunggadewi, 2021)
Corn is one of the major commodities after rice. Efforts to increase corn production face challenges, namely land damage due to excessive and long-lasting use of inorganic fertilizers so that soil health decreases. Therefore, it is necessary to use organic fertilizers to increase soil fertility and elevate plant growth. Organic fertilizers can be used to enhance soil fertility like black grass jelly waste, both solid and liquid. This study aimed to determine the effect of organic fertilizer from black grass jelly waste on solid and liquid at corn plants. The results showed that the use of black grass jelly, both solid and liquid, had a significant effect on the height of corn plants but did not significantly affect the number of leaves of corn plants.